A figurational analysis of teachers and students as policy actors in policy enactment: 'Integrated Learning Experiences' in examinable physical education curriculum. (May 2023) - Scanlon, Dylan; MacPhail, Ann; Calderón, Antonio
Examinable physical education (i.e. physical education as a certificate subject in a high-stakes environment) has distinctive forms of practical and theoretical knowledge, and the concept of 'integration' has been identified as a means to bridge such forms of knowledge. This paper explores how teachers interpret, translate, and enact curriculum policy, particularly the notion of 'integrated learning experiences', and how students respond to 'integrated learning experiences' in the Irish examinable physical education curriculum. Figurational sociology was used to locate the teachers and students in a web of interdependent relationships and conceptualise them as 'policy actors'. Through analysing a year-long data set of teacher and student qualitative data, this paper sheds light on how teachers and students 'do' policy work which we explicitly argue is influenced by the independencies within their figurations in the multi-layered policy enactment context. This paper contributes to our understanding of the policy enactment process and how teachers and students engage (or not) with the enactment of curriculum policy.